Environmental management rivalry and firm performance. Issue 2 (15th May 2017) - Kumar, Anupam; Cantor, David E.; Grimm, Curtis M.; Hofer, Christian
Abstract : Purpose: The purpose of this paper is to build and test theory regarding how rivalry in environmental management (EM) affects a focal firm's environmental image and financial performance. Design/methodology/approach: The theory is tested with an original panel data set of 2, 776 focal-rival dyad pairs. Measures of environmental signals are developed from content analysis of corporate sustainability reports. Environmental performance data are drawn from the Newsweek US 500 Green Rankings database. Financial performance data are drawn from COMPUSTAT. Findings: The main findings are that focal firm signals have a positive and significant impact on both focal firm environmental image and financial performance. Rival firm signals have a negative effect on focal firm environmental image. Surprisingly, rival firm signals have a positive impact on focal firm financial performance. Practical implications: This paper can serve as a testament to the value of monitoring rival firm strategies and signaling to counter the impact of rival signals in the environmental domain. Environmental practices can be a source of competitive advantage for firms, and failure to compete in this space can place the firm at a competitive disadvantage. Originality/value: This study makes several contributions to the EM literature. Leveraging competitive dynamics and the institutional viewpoints, this study builds theory with regard to how signals of competitive EM activity among a focal firm and its rivals affect environmental image and financial performance.